Current agreement on the management of Stevens–Johnson syndrome and toxic epidermal necrolysis. (1st September 2021) - Chen, C.‐B.; Chung, W.‐H.
Abstract: Linked Article: Brüggen et al . Br J Dermatol 2021; 185:616–626 .